CANVA-BASED LEARNING VIDEO-MAKING TRAINING FOR TEACHERS OF SD DHARMA MULIA GETASAN, SEMARANG REGENCY - Putranto, Dwiyono; Suyatno, Tri; Siswoyo, Eko; Setyoko, Rahmad; Mariyono, Ari; Junaidi, Junaidi (LPPM Univ. Ibn Khaldun Bogor, 2024)
Learning videos are audio-visual media that is very useful for teachers in attracting students' attention in the learning process so that the material can be more easily understood. Canva has become a popular application used by teachers to create learning media online. The aim of this community service program is to increase teachers' understanding of learning videos and improve teachers' skills in making learning videos using Canva for teachers at Dharma Mulia Getasan Elementary School, Semarang Regency. Training is carried out using a classical approach through planning, implementation, and evaluation stages. The participants in this training were 9 teachers of Dharma Mulia Getasan Elementary School. The results of the training process evaluation showed that the training participants were very satisfied with the training materials (92%), trainer (84%), and training facilities (88%). The N-Gain calculation produces an effectiveness percentage of 87%, so this training is very effective in increasing teachers' understanding of learning videos. Evaluation of training results shows that participants mastered the Canva application in making learning videos with a percentage of 84%.